Blockchain and IoT Integration in Digitalpreneurship Curricula: A Framework for Enhancing Halal Traceability - Alif Ringga Persada; Rijal Assidiq Mulyana; Abdul Muizz Abdul Wadud Kasyful Anwar; Refaldo Fanther (Politeknik Siber Cerdika Internasional, 2026)
Background: The global halal market is expanding rapidly, yet formal halal certification among Indonesian MSMEs stagnates at approximately 0.08%, reflecting systemic barriers in digital literacy and inefficiencies in manual self-declare compliance systems. Objective: This study aims to reconstruct a digitalpreneurship incubator curriculum through the “Halal Metric” framework, integrating Blockchain and IoT technologies to automate Shariah compliance and enhance end-to-end halal traceability. Methods: Utilizing a mixed-methods R&D design with the ADDIE instructional model, the study developed a pedagogical approach centered on three competency pillars: Halal Digital Presence, Blockchain Integrity, and Smart Contract Verification. The curriculum was pilot-tested with 50 purposively selected MSME tenants from UIN Siber Syekh Nurjati Cirebon’s business incubator. Performance was measured through blockchain transaction logs, verification time benchmarks, and validated Likert-scale surveys assessing administrative burden and consumer trust. Results: The intervention enabled real-time digital traceability, reducing verification time from seven days to under 30 minutes, with 99.8% accuracy in deviation detection. Administrative burdens decreased by 85%, and consumer trust increased by 89% compared to manual baselines. Conclusion: The synergy between digital entrepreneurship education and Halal Metric technology serves as essential trust infrastructure for MSME participation in both national and global halal ecosystems.